1994
DOI: 10.1073/pnas.91.20.9495
|View full text |Cite
|
Sign up to set email alerts
|

Genetic instability in human ovarian cancer cell lines.

Abstract: We have analyzed the stability of microsatellites in cell lines derived from human ovarian cancers and found that 5 out of 10 of the ovarian tumor cell lines are genetically unstable at the majority of the loci analyzed. In clones and subclones derived serially from one of these cell lines (2774; serous cystadenocarcinoma), a very high proportion of microsatellites distributed in many different regions of the genome change their size in a mercurial fashion. We conclude that genomic instability in ovarian tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 33 publications
2
59
1
Order By: Relevance
“…One tumour in our series meets these criteria. RER is often found in colorectal cancers, colon, endometrial (Burks et al, 1994) and ovarian cancers (Orth et al, 1994;Liu et al, 1995). In cervical cancer, two groups (Mitra et al, 1995;Larson et al, 1996) reported microsatellite instability.…”
Section: Discussionmentioning
confidence: 99%
“…One tumour in our series meets these criteria. RER is often found in colorectal cancers, colon, endometrial (Burks et al, 1994) and ovarian cancers (Orth et al, 1994;Liu et al, 1995). In cervical cancer, two groups (Mitra et al, 1995;Larson et al, 1996) reported microsatellite instability.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic instability is a characteristic phenotype of cancer cells. [14][15][16][17][18] Under most circumstances, however, TAAs expressed by malignant cells are insufficiently immunogenic. Effective immune responses that can result in rejection of the …”
Section: Introductionmentioning
confidence: 99%
“…Somatically acquired microsatellite alterations occur frequently in endometrial, gastrointestinal, testicular, colorectal and ovarian carcinomas leading to characterizing these tumors as microsatellite instable (MSI+) or not (MSI7) (Gurin et al, 1999;King et al, 1997;Liu et al, 1995;Orth et al, 1994;Yamamoto et al, 1997). These alterations are correlated with mutations in mismatch repair (MMR) system genes (hMSH2, hMLH1, hMSH6 etc.)…”
mentioning
confidence: 99%